A237 SHARED DECISION MAKING: DESIGN OF A PREGNANCY IN IBD DECISION AID (PIDA) - Williams, A (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Given a significant proportion of women with inflammatory bowel disease (IBD) are of child-bearing age, the development of a pregnancy IBD decision aid would benefit patients and clinicians. Lack of IBD-specific reproductive knowledge has been associated with increased “voluntary childlessness” and may contribute to inappropriate medication changes during or after pregnancy. Decision aids support decision making in pregnancy in general, as well as in multiple other chronic diseases. However existing literature has not identified such a resource for women with IBD. AIMS: To develop a decision aid to improve decision making regarding preconception and pregnancy in IBD among women with IBD. METHODS: We followed the International Patient Decision Aids Standards (IPDAS). A steering committee of Canadian and Australian health care professionals with an interest in IBD management in pregnancy, in addition to patient representatives, was established. Themes chosen for discussion included inheritance, fertility, nutrition, medications, mode of delivery, breastfeeding, infant health. Initial patient and clinician focus groups were conducted and responses recorded with written/audio mediums. We developed an electronic PIDA draft that incorporates individualised information (type of IBD, pre-conception or pregnant, surgical history, medications) in personalized decision making. Further patient focus groups and interviews were conducted to obtain user opinion of the PIDA draft. RESULTS: In July 2017, patient and clinician focus groups were conducted at a Canadian site. Three patients (pre-conception) attended the focus group. Patient concerns - impact of disease and surgery on fertility and preterm delivery; impact of drug therapies on the fetus/ infant; impact of active disease on maternal and fetal/infant health. The clinician focus group included 3 IBD specialists, 2 IBD fellows, 2 IBD nurses, an obstetrician and a neonatal intensivist. Clinician concerns - absence of pre-conception counselling and lack of patient understanding about the impact of disease activity and IBD medication use in pregnancy. Additional patient feedback obtained through interviews (n=15) at two Canadian sites since March 2019 regarding the current electronic PIDA was positive, with comments about content, personalization, readability and unbiased presentation. Suggestions were made for inclusion of additional content such as impact of IBD on sexual function, laboratory changes during pregnancy, and timing of medications post-partum. CONCLUSIONS: The pre and post PIDA design patient and clinician focus groups and interviews affirmed the role for PIDA. Main decisions considered necessary to address included ideal timing of conception pending disease activity, management of medications, and delivery methods. Ongoing user feedback will be obtained at Australian and Canadian sites during planned alpha testing. FUNDING AGENCIES: WCHRI, Sinai Health System, UBC